ANGKOLA BATAK TRADITION: ISLAM, PATRILINEALITY, MODERNITY: Reviving and Challenging - Muhammad Habibi Siregar (Pascasarjana Universitas Wahid hasyim Semarang, 2015)
Identity attached in a group always coincides with the perception within it. Identity of general Batak society is perceived as the masculine identity created the gap between female and male in term of the social and economy resources. Batak society who live outside of Bonapasogit likely more solid than they live in Bonapasogit. Itcan be proved by the intense meeting internal Batak community more often than in Bonapasogit. Due the penetration from other cultures force them who reside out Bonapasogit more united among them. Meanwhile, for people live in Bonapasogit the only threat coming from their own community because they didn’t face the penetration from outsiders. Especially, for female Batak community the threat is the dominating patrilineality who standstill the tradition which isn’t favored to female. In densely population in cities, marga can be used as the supported tools in relationship even many female Batak were born outside Bonapasogit still use marga for their advantage purpose, especially in bureaucracy. Meanwhile for Angkola Batak who live their hometown has the different situation due don’t get advantage the beneficiary of marga. Because of pressure from their own community Keywords: Islam; patrilineality; inheritance; human right; identity